Improvement of Lipoplexes With a Sialic Acid Mimetic to Target the C1858T PTPN22 Variant for Immunotherapy in Endocrine Autoimmunity - Arena, Andrea; Belcastro, Eugenia; Ceccacci, Francesca; Petrini, Stefania; Conti, Libenzio Adrian; Pagliarosi, Olivia; Giorda, Ezio; Sennato, Simona; Schiaffini, Riccardo; Wang, Peng; Paulson, James C.; Mancini, Giovanna; et al. (Frontiers in Immunology, 2022)
The C1858T variant of the protein tyrosine phosphatase N22 (PTPN22) gene is associated with pathophysiological phenotypes in several autoimmune conditions including Type 1 diabetes and autoimmune thyroiditis. The R620W variant protein, encoded by C1858T, leads to a gain of function mutation with paradoxical reduced T cell activation. We previously exploited a novel personalized immunotherapeutic approach based on siRNA delivered by liposomes (lipoplexes, LiposiRNA) that selectively inhibit variant allele expression. In this manuscript, we functionalize lipoplexes carrying siRNA for variant C1858T with a high affinity ligand of Siglec-10 (Sig10L) coupled to lipids resulting in lipoplexes (LiposiRNA-Sig10L) that enhance delivery to Siglec-10 expressing immunocytes. LiposiRNA-Sig10L lipoplexes more efficiently downregulated variant C1858T PTPN22 mRNA in PBMC of heterozygous patients than LiposiRNA without Sig10L. Following TCR engagement, LiposiRNA-Sig10L more significantly restored IL-2 secretion, known to be paradoxically reduced than in wild type patients, than unfunctionalized LiposiRNA in PBMC of heterozygous T1D patients.